Protocols for the obvious: Where does it start, and stop? - Armand R. J. Girbes; Paul E. Marik (Annals of Intensive Care, 2017)
Abstract Protocols can be helpful in specific situations and may have show benefits in clinical trials. So-called evidence based protocols and checklists frequently remind clinicians to do the obvious, but may also contain as part of a bundle, elements that are not based on the best current evidence. However, so called quality improvement programs frequently call for implementation of the total bundle. We think this is basically wrong and warn against that practice.